Enhanced photoelectrocatalytic performance of α-MnO2 by Sb and N charge compensation. (18th November 2021) - Guo, Minmin; Yang, Huimin; Du, Yuting; Wang, Yingjin; Yang, Xiaojing
Abstract : The donor Sb and acceptor N can promote the separation of electron–hole pairs excited by photoirradiation. Abstract : The photoelectrocatalytic performance of (Sb, N)–MnO2 is explored by experiment and first principles calculation based on density functional theory. The photoelectrochemical performance test shows that 6% (Sb, N)–MnO2 with a maximum electrochemically active area and minimum charge transfer resistance has an oxygen evolution potential of 1.59 V. At this ratio, the photocurrent density reaches 8.00 mA cm −2 and the degradation rate is 87.89%. Furthermore, the possible role of Sb and N doping in modifying the photoelectrocatalytic performance is studied theoretically. The band gap decreases from 0.944 eV to 0.203 eV due to the formation of the charge compensation effect, which is conducive to the photoelectrocatalytic performance. The theoretical predictions agree well with the experimental results, which can provide an ideal alternative material for wastewater treatment.